A Guide to practitioner research in education - Menter, Ian; Elliot Dely ;Hulme Moira ;Lewin Jon ;Kevin Lowden (Thousand Oaks, California : Sage Publications, Incorporation, 2011)
This text is a guide to research methods for practitioner research. Written in friendly and accessible language, it includes numerous practical examples based on the authors' own experiences in the field, to support readers.
Part 1. What is research and why do it? -- Part 2. What do we want to know -- Part 3. What do we know already and where do we find it? -- Part 4. How will we find out? -- Part 5. What does it mean? -- Part 6. How will we tell everyone?.
Includes bibliographical references and index.
Keywords: EDUCATION